DIRECT CONNECTION OF STEREOTYPICAL CONCEPTS WITH CULTURE AND SOCIETY IN LITERARY TRANSLATION - Toshtemir Alimov (Bright Mind Publishing, 2025)
The article describes the direct connection of stereotypical concepts with culture and society in literary translation. A stereotype is an opinion formed or learned by external factors that reflects the beliefs of a person or a member of a certain society and how he behaves and fulfills the requirements of written or unwritten rules of a certain group. Stereotypes may not always reflect reality, but stereotypes begin to form from the day a person is born. Stereotypes are directly related to culture.
Keywords: Stereotypes, measure, standard, model, racial, cultural gender stereotypes, language culture.